2011
DOI: 10.1017/s002966511100228x
|View full text |Cite
|
Sign up to set email alerts
|

Taste enhancement of savoury food aiming to increase acceptance by an elderly cohort

Abstract: Diminished sensory ability, and specifically smell and taste deterioration caused by ageing or due to medication and illness, is one common factor which contributes to malnutrition within older adults (1) . However, it has been shown from previous studies that flavour enhancement of food using monosodium glutamate and/or added flavours resulted in increased food intake among sick and healthy elderly individuals (2) .The aim of this study was to increase the liking of food for older adults by enhancing the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
1
1
Order By: Relevance
“…Seventeen studies found taste-identification thresholds to increase with age, although one study reported only a weak relationship between age and taste strip results (52) . Only one study found no significant difference between age groups (53) ; however, their older group was younger than in all other studies reported in this review (age [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65], and therefore outside of our inclusion criteria. (27) 18 34 37 65-78 55-65 ME NaCl, SU (6) NaCl P < 0 .…”
Section: Effects Of Ageing On Taste Identification Thresholdscontrasting
confidence: 58%
See 1 more Smart Citation
“…Seventeen studies found taste-identification thresholds to increase with age, although one study reported only a weak relationship between age and taste strip results (52) . Only one study found no significant difference between age groups (53) ; however, their older group was younger than in all other studies reported in this review (age [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65], and therefore outside of our inclusion criteria. (27) 18 34 37 65-78 55-65 ME NaCl, SU (6) NaCl P < 0 .…”
Section: Effects Of Ageing On Taste Identification Thresholdscontrasting
confidence: 58%
“…While deterioration in salt perception should not be compensated for by the addition of extra salt in food for elderly people who may already be at risk of hypertension, CVD or hypernatraemia, authors have suggested that increased levels of umami tastants can improve liking and consumption of foods by older adults. Although this has typically been achieved through the direct addition of monosodium glutamate (2) , it can also be achieved through the use of natural ingredients rich in umami taste compounds (65) . Sensory decline is a generic process and happens to everyone, yet several factors can influence the extent of this sensory decline.…”
Section: Resultsmentioning
confidence: 99%